Relationship between physical activity and chronic obstructive pulmonary disease: a cross-sectional study - Kou, Ziwei; Wang, Yaoyao; Hao, Wanming; Li, Yanmiao; Yu, Xinjuan; Li, Yinan; Zhong, Yulu; Gong, Entong; Wang, Tao; Han, Wei (Frontiers in Public Health, 2025)
BackgroundThis study explores the association between physical activity (PA) levels and patterns during adulthood and chronic obstructive pulmonary disease (COPD).MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2007–2018 was analyzed. A total of 34,392 participants were included. Three physical activity levels groups were categorized: insufficiently active (individuals not meeting the criteria for “Sufficiently active” or “HEPA active”), sufficiently active ((≥3 days of vigorous activities (≥480 MET-min/week), or ≥5 days of moderate activities /walking (≥600 MET-min/week), or ≥5 days of combined activities (≥600 MET-min/week)), HEPA active ((≥3 days of vigorous activities (≥1,500 MET-minutes/week), or ≥7 days of combined activities (≥3,000 MET-min/week)). Five PA patterns groups were categorized: vigorous work activity, moderate work activity, walk/bicycle for transportation, vigorous recreational activity, moderate recreational activity. The relationship between PA and COPD was explored using a multivariable logistic regression model, restricted cubic spline (RCS) analysis, and stratified analysis.ResultsCompared to insufficiently active individuals, being sufficiently active (OR: 0.86, 95% CI = 0.75–0.98, p = 0.025) and HEPA active (OR: 0.84, 95% CI = 0.73–0.96, p = 0.010) were associated with lower COPD prevalence. Compared to those lacking corresponding PA patterns, low-level (OR: 1.35, 95% CI = 1.12–1.62, p = 0.002) and sufficient (OR: 1.19, 95% CI = 1.05–1.35, p = 0.006) moderate work activities (OPA) were linked to higher COPD prevalence. Sufficient transportation-related physical activities (TPA) (OR: 0.72, 95% CI = 0.59–0.89, p = 0.003), sufficient vigorous recreational activities (RPA) (OR: 0.68, 95% CI = 0.55–0.85, p < 0.001), low-level moderate RPA (OR: 0.77, 95% CI = 0.66–0.90, p = 0.001), and sufficient moderate RPA (OR: 0.71, 95% CI = 0.61–0.84, p < 0.001) were all significantly associated with lower COPD prevalence.ConclusionIn adulthood, TPA and RPA were associated with a lower COPD prevalence, while OPA were associated with a higher COPD prevalence. However, COPD patients might become less active because of their symptoms, which may influence study results. Increasing TPA/RPA proportion in total PA could be a potential COPD prevention strategy, but causal evidence requires further validation.